2022
DOI: 10.1002/ppsc.202100264
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress and Future Perspectives of Carbon Dots in the Detection, Degradation, and Enhancement of Drugs

Abstract: for maximum solar energy conversion. Due to the broad light absorbance, photo luminescence (PL) properties, and elec tron transfer capability, CDs alone and as composites with other species can act as excellent candidates for the degradation of organic pollutants. CDs have a healthy competition between traditional semicon ductors in several aspects such as reduced cost, easy functionalization, biocompat ibility, highly tunable PL, inertness, and resistance to photobleaching, in which CDs are almost in the winn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 182 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…It was reported that the existence of CDs in most cases could not be confirmed by XRD spectra, due to the low crystallinity and high dispersion of CDs [ 8 ]. In the future, the use of appropriate characterization methods is quite important for the research of CDs-based materials.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the existence of CDs in most cases could not be confirmed by XRD spectra, due to the low crystallinity and high dispersion of CDs [ 8 ]. In the future, the use of appropriate characterization methods is quite important for the research of CDs-based materials.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…Han et al [ 7 ] summarized the advances in CDs-based ratiometric fluorescent sensors for food safety applications and detection mechanisms. Korah et al [ 8 ] reviewed three aspects of CD-drug interactions, including drug detection, photocatalytic degradation by CDs-based composites, and enhancement of drugs by using CDs. Mohammadi [ 9 ] reported the recent progress in using carbon-based QDs as a biosensing and fluorescence imaging platform for the early stage diagnosis of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining clear solutions were diluted with related buffer media (1 to 100 mL) and studied on a UV-vis spectrophotometer at a wavelength of 295 nm. 21,62,63 2.4. Cellular experiments 2.4.1.…”
Section: Drug Release Experimentsmentioning
confidence: 99%